2004
DOI: 10.1101/gad.284704
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor function in hepatocytes is essential to promote postnatal body growth

Abstract: Mice carrying a hepatocyte-specific inactivation of the glucorticoid receptor (GR) gene show a dramatic reduction in body size. Growth hormone signaling mediated by the Stat5 transcription factors is impaired. We show that Stat5 proteins physically interact with GR and GR is present in vivo on Stat5-dependent IGF-I and ALS regulatory regions. Interestingly, mice with a DNA-binding-deficient GR but an unaltered ability to interact with STAT5 (GR dim/dim ) have a normal body size and normal levels of Stat5-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 48 publications
5
109
0
Order By: Relevance
“…Plasma corticosterone levels are high at delivery and rapidly decline during the first 24 h after birth, and epinephrine and norepinephrine levels are increased severalfold in newborns in response to the stresses of birth, such as transient hypoxia, cold exposure, and cord cutting (15). Because GC plays a critical role in the maintenance of neonatal blood glucose levels through the induction of gluconeogenesis, one-half of hepatocyte-specific GC receptor KO mice die shortly after birth as a result of hypoglycemia (17). Here, we demonstrated that MC2R KO mice are defective in this adaptation, consistent with a previous report that 75% of POMC KO mice die shortly after birth (2).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma corticosterone levels are high at delivery and rapidly decline during the first 24 h after birth, and epinephrine and norepinephrine levels are increased severalfold in newborns in response to the stresses of birth, such as transient hypoxia, cold exposure, and cord cutting (15). Because GC plays a critical role in the maintenance of neonatal blood glucose levels through the induction of gluconeogenesis, one-half of hepatocyte-specific GC receptor KO mice die shortly after birth as a result of hypoglycemia (17). Here, we demonstrated that MC2R KO mice are defective in this adaptation, consistent with a previous report that 75% of POMC KO mice die shortly after birth (2).…”
Section: Discussionmentioning
confidence: 99%
“…In liver, GR is recruited to STAT5 regulated genes such as insulin-like growth factor 1, and is required for normal post-natal growth. Importantly, this GRmediated transcriptional control is intact in liver cells expressing only GR dim (Tronche et al, 2004). In a similar fashion, STAT3 and GR can physically interact and cooperate to activate promoters containing either STAT or GR binding sites (De Miguel et al, 2003;Kordula and Travis, 1996;Lerner et al, 2003;Takeda et al, 1998;Zhang et al, 1997).…”
Section: A Clarkmentioning
confidence: 99%
“…In transfected cells GR dim is capable of inducing at least some GC target genes (Rogatsky et al, 2003), cooperative gene regulation by GCs and STAT5 is spared in the GR dim mouse (Tronche et al, 2004), and at least one antiinflammatory mediator is effectively induced by GCs in murine macrophages expressing only GR dim (Abraham et al, 2006). In the absence of microarray data describing global transcriptional changes in cells expressing GR dim , it is too early to conclude how broadly and how strongly the induction of gene expression by GCs is impaired, therefore it remains a strong possibility that this mutation does not A c c e p t e d M a n u s c r i p t…”
Section: Evidence In Favour Of Transrepressionmentioning
confidence: 99%
“…The biological consequences obtained upon the loss of a single transcription factor are probably not only due to a loss-of-function but also due to a gainof-function by other recruited signaling pathways. In addition, because Stat5 interacts either directly or indirectly with other regulatory molecules, such as the glucocorticoid receptor 26 and the hepatocyte nuclear factor 4a, 27 loss of Stat5 might also affect biological responses initiated by these molecules. Thus, developmental and physiological changes observed upon the loss of a single transcription factor are likely the result of a greatly disturbed regulatory network.…”
Section: Molecular Networkmentioning
confidence: 99%